Firman Menginspirasi, Nyanyian Menyaksikan: Menguatkan Iman dan Pelayanan di Resort GKE Tumbang Samba - Tahan Mentria Cambah; Gabriella Tara Yohanessa (Akoloutheo: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Kursus Teologi Warga Gereja (KTWG) or Church Members’ Theological Course in the GKE Tumbang Samba Resort serves as a platform for theological learning that aims to deepen and contextualize the faith understanding of church members. Through two main topics: The Old Testament: From Ancient Text to Present Reality and Witnessing Through Songs/Hymns, this program invites participants to bridge the heritage of biblical faith with the dynamics of contemporary worship. The discussion on the relevance of the Old Testament helps believers view God’s Word not as a distant ancient text but as a living source of values that speak into daily life. Meanwhile, the reflection through Songs/Hymns opens space for dialogue on sincere, contextual, and Christ-centered worship. The KTWG thus becomes a means of spiritual and theological formation that enriches church life, encourages active participation of members, and strengthens a faith grounded in critical understanding and genuine love.